Physical Interaction as a Game: A Review - Kowalski, Andrés Mauricio (2015)
Recent work on classical-quantum games is reviewed. We present in game-theory terms the physics associated to the interaction between matter and a single-mode of an electromagnetic field within a cavity, introducing a game admitting of both classical and quantal players. Strategies are determined by the initial conditions of the associated dynamical system, whose time evolution is characterized by the existence of attractors that set the possible results of the game. Two types of quantum states are considered; perfectly distinguishable or partially overlapping ones.